Intestinal parasitic infections in pregnancy – A review. (November 2020) - Mohan, Suruchi; Halle-Ekane, Gregory; Konje, Justin C.
Abstract: Intestinal parasitic infections are widespread worldwide and with increased global travel and transport of food, these are not entirely limited to traditionally endemic areas. The prevalence of parasitic infections in endemic areas among pregnant women ranges from 24 to 70 % with approximately 10 % of women having multiple parasites. Pregnancy with its increased nutritional demands and altered immunological defenses is an especially vulnerable time for acquiring parasitic infections, which may be associated with adverse outcomes such as anaemia, which in some cases may even contribute to mortality. The presence of a helminthic infections during pregnancy may also cause immunological effects that can contribute to maternal morbidity and mortality as well as affecting the maternal immune response and immune system function in the baby after birth. Mass administration of anthelminthic drug therapy has been applied in endemic areas but there is inconclusive evidence of its benefit in improving pregnancy outcomes, however, no safety concerns have been highlighted with the use of the recommended drugs for parasitic infections.